Key concepts in historical geography - Morrissey, John; Nally, David; Strohmayer, Ulf (Key concepts in human geography, 2014)
Edited by Dr Rob Kitchen, Director of the National Institute of Regional and Spatial Analysis (NIRSA) at the National University of Ireland, the Key Concepts in Human Geography series is an innovative set of companion texts for undergraduate students of the Human Geography sub-disciplines. Organized around 20 short essays, they provide a cutting edge introduction to the central concepts that define contemporary research in their field. All books in the series are authored by internationally recognized academics and include an introductory chapter and extensive pedagogic features in the form of a glossary, figures, diagrams and further reading. Morrissey et al have produced a detailed yet expansive guide to an area in which students have been poorly served in the past. Key Concepts in Historical Geography ..